2016
DOI: 10.1007/s13239-016-0279-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Leaflet Design on Transvalvular Gradients of Bioprosthetic Heart Valves

Abstract: Bioprosthetic aortic valves (BAVs) are becoming the prostheses of choice in heart valve replacement. The objective of this paper is to assess the effects of leaflet geometry on the mechanics and hemodynamics of BAVs in a fluid structure interaction model. The curvature and angle of leaflets were varied in 10 case studies whereby the following design parameters were altered: a circular arch, a line, and a parabola for the radial curvature, and a circular arch, a spline, and a parabola for the circumferential cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Structurally, the cross-section of a leaflet of aortic valve is a tri-layered structure composed of fibrosa, spongiosa, and ventricularis responsible for the anisotropic mechanical behavior of the valvular tissue in the direction as well as across the layers [19,20]. Finite element analysis has shown that the principal load is supported in the circumferential direction during diastole and compressive forces are confined only to the boundaries [21,22]. Therefore, hybrid scaffolds in the present study could potentially be exploited for mimicking a load bearing layer, with the fibrosa as a preliminary model for TEHV, and have been studied under the effect of compressive and viscoelastic forces.…”
Section: Introductionmentioning
confidence: 99%
“…Structurally, the cross-section of a leaflet of aortic valve is a tri-layered structure composed of fibrosa, spongiosa, and ventricularis responsible for the anisotropic mechanical behavior of the valvular tissue in the direction as well as across the layers [19,20]. Finite element analysis has shown that the principal load is supported in the circumferential direction during diastole and compressive forces are confined only to the boundaries [21,22]. Therefore, hybrid scaffolds in the present study could potentially be exploited for mimicking a load bearing layer, with the fibrosa as a preliminary model for TEHV, and have been studied under the effect of compressive and viscoelastic forces.…”
Section: Introductionmentioning
confidence: 99%
“…ALE has been used in many studies of AHVs with rigid leaflets as listed in Section 4, however to the best of the authors’ knowledge, it has been limitedly applied to simulate the dynamics of heart valves with elastic leaflets in the past literature. Dabiri et al 110 investigated the effect of 10 different designs of linearly elastic leaflets of bioprosthetic heart valves on the transvalvular gradients using ALE. However, the mutual coaptation between the leaflets and the sinuses of aortic root were not modeled in this study, which can influence the leaflet kinematics and consequently the numerical stability.…”
Section: Numerical Fsi Methodsmentioning
confidence: 99%
“…In modern medical science, numerical methods of simulating the work of heart valve bioprostheses are being actively used at the stages of their design and optimization as the recognized tools of an in-depth engineering analysis [1][2][3][4]. The main motivation of in silico studies is to increase the lifetime of the prostheses [5,6] functioning under the condition of a long-term load in the recipient organism and to improve their hemodynamic performance [1,2,7]. The literature shows a direct dependency of pathological mineralization and fatigue-induced deterioration of the leaflet apparatus on the stress and strain amplitudes in its material [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Numerical simulation requires indispensable simplification of the problem statement: some assumptions in the material behavior, reduction of the border conditions and geometry, whose application validity must be grounded qualitatively and quantitatively in comparison with a natural in vitro or in vivo experiment [ 16 , 17 ]. A number of articles on the numerical simulation directed to the search for an optimal leaflet apparatus geometry of the cardiac valve prostheses reproduce the basic functional of its work [ 1 , 2 , 7 , 18 , 19 ], although fail to provide minute qualitative repetition of the intricate effects and show qualitative disagreement of the results with the experiment. The biomechanics of bioprosthetic valve components for hydrodynamic damping in the diastolic phase may be referred to such a complicated problem [ 20 ].…”
Section: Introductionmentioning
confidence: 99%